The Six-Port Structure as a Precise Measurement Tool - A New Rise of an Old Concept - Kölpin, Alexander; Lindner, Stefan; Mann, Sebastian; Barbon, Francesco; Talai, Armin; Weigel, Robert (Kleinheubacher Tagung, 2013)
Six-Port Technique has been known in RF and microwave metrology since the early 1970s for vector network analysis and precise power measurements. Two decades later, the system has been proposed as a receiver for complex valued data reception. However, six-port technique has always been niche architecture, since the tremendous evolution in integrated circuit technology got more and more impact on high-end circuitry and measurement systems. But there are some special applications that can be very efficiently addressed by the six-port principle. In general, all scenarios where the interesting information is coded in signal power or can be translated in relative phase shifts are suitable for six-port systems, as this architecture offers superior phase resolution combined with low cost implementation. Furthermore, this principle can be used up to millimeter-wave frequencies and even higher. The reason is that the core functionality is realized only by passive transmission lines or waveguide structures featuring the interferometric part, and only diodes have to be used as monolithic components for the RF front-end. The information reconstruction is conducted in baseband by algorithms with very low complexity that can be run on a low power microcontroller and show only low latency of a few controller clock cycles. In this talk the newest results for applications addressed by six-port architecture for metrology will be presented. Besides very precise distance and angle measurements or vibration analysis, like heartbeat and breath rate detection, also new fields will be presented. One very promising approach is using the six-port technique for frequency analysis of a pulse-like microwave signal. Furthermore, the very first results in temperature measurements of a water basin by a six-port reflectometer will be shown.
elib2cris::1512001600,koelpin2013c
Keywords: Six-Port; Interferometer